Co-administration of routine paediatric vaccines in England often deviates from the immunisation schedule. (December 2021) - Bauwens, Jorgen; de Lusignan, Simon; Sherlock, Julian; Ferreira, Filipa; Künzli, Nino; Bonhoeffer, Jan
Abstract: Vaccine co-administration can facilitate the introduction of new vaccines in immunisation schedules and improve coverage. We analysed real life data to quantify the extent of routine paediatric vaccine co-administrations as recommended and as never recommended in the immunisation schedule in England, and assessed factors for recommended and never recommended vaccine co-administrations. Immunisation data for all scheduled routine paediatric vaccines between 2008 and 2018 was obtained from the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC). We included 6′257′828 doses administered to 1′005′827 children. Twenty-one percent of vaccines were given separately, 79% were co-administered. Sixty-four percent of vaccines scheduled for co-administration were co-administered as recommended while 15% were administered separately. Among all vaccine co-administrations, 75% happened as recommended in the schedule, 4% were never recommended, while 21% deviated from the schedule. Vaccine co-administration according to the schedule varied greatly between vaccines. Forty-eight percent of English children received at least one of their vaccine co-administrations not as recommended in the immunisation schedule, with 19% of children receiving none of their co-administered vaccines as recommended. Late administration of one or more vaccines increased the odds for deviated co-administrations (OR 1.60) and strongly increased the odds for never recommended co-administrations (OR 5.34). Differences between genders, NHS regions, and IMD quintiles were statistically significant but small. Suboptimal co-administration rates for routine paediatric vaccines are a missed opportunity and should be optimised by concerted public health action.